DISTRIBUTION OF BALEEN WHALES IN THE SOUTHERN HEMISPHERE (K Raspredeleniyu Usatykh Kitov v Yuzhnom Polusharii) - Zemskii,V. A. (1970)
A total of 7 pods of fin whales and 4 pods of sei whales have been investigated. The largest group of fin whales consisted of 246 individuals; the smallest one consisted of 34 individuals. The largest group of sei whales contained 226 individuals, while the smallest one had 16 individuals. By analyzing these concentrations, it appears that they are formed on the basis of age and physiological properties; sexually mature individuals of both sexes, which reproduce during the current season, form special groups; the individuals that reach sexual maturity and are barren from other groups. To obtain a more accurate classification of biological groups, and clarity of the rules governing their formation and distribution, it is necessary to have more data. (Author) Trans of mono. Morskie Mlekopitayushchie, Moscow, 1965 p20-26, by M. Slessers.